FEASIBILITY OF STEM-APPROACHED WORKSHEET TO IMPROVE STUDENTS ’LEARNING OUTCOMES - Nuzula, Ega Firdausi; Fauziah, An Nuril Maulida (PENSA E-JURNAL: PENDIDIKAN SAINS, 2020)
This study aims to describe the feasibility of the STEM-approached Worksheets to improve student learning outcomes on liquid pressure material. The feasibility of the worksheet is evaluated by the aspects of validity, practicality, and effectiveness. This worksheet was developed by using the ADDIE model. The subjects of this study were 30 students of class VIII-B of Junior High School 1 Wonosalam. The results of the validity aspects showed that the worksheet validation score was 4 with very valid criteria. The result of the practicality aspects shows the implementation of learning by using STEM-approached worksheets obtaining mode 4 with very good categories and very good student activities. The highest percentage of student activity is 26.77%, which is doing worksheets by conducting experimental activities and making STEM products in the form of Bottle Raft. The results of the effectiveness aspects based on an increase in student learning outcomes showed an average N-Gain score of 0.71 with a high category. Based on the posttest score, there was 83% of students completed and 17% of students did not complete. Students respond very well to STEM-approached worksheets. Based on the results of this study, it can be concluded that the STEM-approached Worksheets are feasible to improve student learning outcomes.